Lifelong Learning in the Perspective of Hadith: Implementation and Its Relevance in Modern Life - Imam Adilan, Dilan; Mu'min, Mu'min (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
This article examines the concept of lifelong learning from the perspective of hadith and its relevance to modern educational challenges. The hadith, "Seek knowledge from the cradle to the grave," emphasizes the importance of continuous education without age or time restrictions. Though some scholars debate the authenticity of this hadith, its moral value remains relevant, encouraging lifelong learning, both formally and informally. The article also discusses how Islamic education not only focuses on religious knowledge but also encompasses general knowledge for the welfare of humanity. It explores the integration of Islamic values with modern education, especially in the era of digitalization and globalization. By combining religious principles and modern technological advancements, lifelong learning in Islam remains a vital tool for self-improvement and societal benefit. This study concludes that lifelong learning is a holistic concept in Islam, encompassing both worldly and spiritual aspects, and remains r